Evaluation of the Success of the Anemia Prevalence Reduction Program - Laminah Laminah; Endah Mulyani; Amalia Rahma; Dwi Novri Supriatiningrum; Eka Sri Rahayu Ariestiningsih (Indonesian Journal of Global Health Research, 2025)
Anemia is a disease in which the hemoglobin (Hb) level within the blood is lower than ordinary and shifts concurring to age bunch, sex and physiological condition. For adolescent girls (rematri) anemia is considered if Hb <12 gr/dl. This study was to evaluate the success of the anemia prevalence reduction program in Lamongan district Method: The type of research used was quantitative descriptive with a survey research design. The population used in this study were all female adolescent students in grades 7 and 10 in the working area of the Lamongan Regency Health Center. Data collection was carried out by administering questionnaires and examining hemoglobin levels. The data obtained will be analyzed descriptively to determine the characteristics of the sample and presented in the form of frequency distribution and percentage. The results showed that the majority of female adolescents had received iron supplement tablets (TTD) (80.18%), but only 73.29% consumed them according to recommendations. Most female students in grades 7 (90.13%) and 10 (93.05%) had been screened for anemia. The prevalence of anemia in 7th grade female students was 18.68% and 10th grade female students was 18.22%. Conclusions: The FERRAMEG program (FE Hari Rabu Megilan) in the working area of the Lamongan Regency Health Center is considered to have an influence in reducing the prevalence of anemia in female adolescents, indicated by the increasing number of adolescents who consume iron supplement tablets and the number of anemia in adolescents in grades 7 and 10, the majority of whom do not experience anemia and the number of female adolescents who have received screening for anemia.